Analysis of physical education in MAS Istiqomah Sri Gunting (perspective of Islamic education philosophy) - Rusdi, Muhammad; Salaminawati, Salaminawati; Usiono, Usiono; Naldi, Anri (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This study aims to analyze physical education conducted at MAS Istiqomah Sri Gunting based on the perspective of Islamic education philosophy. This research is qualitative research with a phenomenological approach, and the tools used as data collectors are observations, interviews, document studies, and data analysis techniques through data collection steps, data reduction, data presentation, conclusion: Withdrawal/Verification, and validity testing. The results showed that the purpose of physical education at MAS Istiqomah Sri Gunting had not been based on the philosophy of Islamic education because it has not entirely followed health rules in dressing, following health rules about housing, maintaining hygiene, treating diseases, getting used to exercising and regulating eating and drinking patterns. The purpose of physical education is carried out based on the objectives of the educational curriculum used today as recommended by the government. This is reinforced by the absence of learning materials or actions that lead to the habits advocated through the Qur'an and hadith, as well as the opinions of scholars. As the hadith recommended, there were no student learning activities in archery, horse riding, or swimming. So it can be concluded, based on the analysis of the philosophy of Islamic education physical education conducted at MAS Istiqomah Sri Gunting, the objectives and implementation cannot be said to be sourced from the Quran, hadith, and the opinions of scholars as the source of Islamic educational philosophy.